How Applying Soft Lean Components Can Contribute to Reducing Costs in the Service Sector: The Case of Al-Ahliyya Amman University - Ahmad Yousef Areiqat; Ahmad Zamil (International Journal of Supply Chain Management, 2019)
This research aims to identify the rules of lean system application in the service industry. It also seeks to highlight the requirements of applying the lean production system on Al-Ahliyya Amman University to reduce costs. The research was conducted in the form of a case-study in Al-Ahliyya Amman University. Data was collected through discussions with some the officials in the university. Including the HR manager, the financial manager, the student affairs manager, and the student registration manager. The results showed that lean production was most successful in service organisations that depend on the core components of lean; such as continuous improvement, problem-solving, decision-making, knowledge management, and technology usage. These components together can be a critical key to reducing costs which is what Just-in-time technique aims to do.